Blended and Collaboration-Based Learning Management Model to Enhance Mobile Website User Experience (UX) Design Skills - Oraboot Wuttikamonchai; Paitoon Pimdee; Kwantitsara Apisuksakul; Aukkapong Sukkamart (Journal of Higher Education Theory and Practice, 2024)
This study presents a collaborative learning model designed to enhance mobile website design skills with a focus on user experience (UX). The model, assessed by nine experts across utility, feasibility, propriety, and accuracy, demonstrates high-quality scores, reflecting substantial agreement and effectiveness. Specific strengths include the model’s adaptability to the curriculum (4.56) and its applicability to university students (4.44). Areas for improvement, with mean values of 3.89, highlight opportunities for refinement, particularly in the appropriateness of learning processes and the precision of details within activities. Synthesizing steps from cooperative, blended, and Project-Based Learning, the model aligns with Stufflebeam’s framework, emphasizing high feasibility, utility, propriety, and accuracy. Comparative insights with previous research validate its strength across diverse educational contexts. The model’s success, proven through evaluation and refinement, carries significant implications for education by enhancing both technical skills and a holistic understanding of user experiences in mobile web design. Despite acknowledged limitations, the collaborative learning model invites continued exploration and adaptation, ensuring its relevance in the evolving landscape of educational practices.
Keywords: Technology-Enhanced Education Studies; Educational Technology and E-Learning; Mobile Learning in Education